The impact of dosing sequence on the removal of the persistent pesticide metaldehyde using powdered activated carbon with coagulation and clarification - López, Sara Sánchez; MacAdam, Jitka; Biddle, Mark; Jarvis, Peter (Elsevier, 2020)
Removal of pesticides from drinking water remains a challenge for water treatment suppliers throughout the world. A combined treatment of dissolved air flotation (DAF) and powdered activated carbon (PAC) was investigated as a treatment process for removal of the recalcitrant pesticide metaldehyde. The PAC dosing position relative to the coagulant was studied regarding its impact on the removal of NOM and pesticide, floc formation and the clarification efficiency. Four different water sources were spiked with the pesticide and treated using PAC. A PAC dose of 100 mg/L using a contact time of 20 min was required in order to effectively remove pesticide to the compliance concentrations for all of the water sources. The pesticide adsorption rate (kmet) decreased as the source water DOC increased, moving from 79.5–21.0 mg/μg/min with an increase in DOC from 2.6 to 6.5 mg/L. When combined with coagulation, the sequence of addition of PAC followed by coagulant was most effective due to increased incorporation of PAC into the floc, large floc size (median floc size 800 μm) and a high level of pesticide removal, reducing the metaldehyde concentration to 0.18 μg/L. Limited incorporation of PAC into flocs was observed when the adsorbent was added after the coagulant. The results provide a rational basis for selection of process conditions for pesticide removal using PAC and clarification.
Keywords: Powdered activated carbon(PAC); Adsorption; Flocpesticide; Clarification